A Review: Per- and Polyfluoroalkyl Substances—Biological Degradation - Grgas, Dijana; Petrina, Ana; Štefanac, Tea; Bešlo, Drago; Landeka Dragičević, Tibela (Toxics (Basel), 2023)
Per- and polyfluoroalkyl substances (PFASs), highly stable synthetic organic compounds with multiple carbon-fluorine bonds, are emerging as environmental contaminants, toxic, bioaccumulative, and environmentally persistent. PFASs are strongly resistant to biological and chemical degradation, and therefore PFASs present a challenge to researchers and scientists for a better understanding and application of remediation methods and biodegradation of PFASs and have become subject to strict government regulations. The review summarizes the recent knowledge of bacterial and fungal degradation of PFASs, as well as the enzymes involved in the processes of transformation/degradation of PFASs.